Samuel Taylor Coleridge, the critical heritage - Jackson, J. R. de J. (James Robert de Jager) (Routledge, 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Criticism and interpretation.; Coleridge, Samuel Taylor, -- 1772-1834; POETRY -- English, Irish, Scottish, Welsh.; Criticism, interpretation, etc.